2013
DOI: 10.4269/ajtmh.12-0174
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiologic Survey for Coxiella burnetii Among US Military Personnel Deployed to Southwest and Central Asia in 2005

Abstract: Abstract. We used a seroepidemiologic study to estimate Q fever (Coxiella burnetii) seroprevalence, seroincidence, and risk factors for seroconversion in two deployed military populations in 2005. The first study group resided in an area with a known Q fever outbreak history (Al Asad, Iraq). Of this population, 7.2% seroconverted for an incidence rate of 10.6 seroconversions per 1,000 person-months. The second population included personnel transiting through Qatar on mid-deployment leave from southwest/central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In the Arabian Peninsula, the presence of C. burnetii in humans was reported in 1968, and a recent serological analysis detected C. burnetii Ig in 35.2% of patients with pyrexia of undetermined cause (83)(84)(85). In Qatar, Q fever data are rare, yet a seroprevalence of 2.1% was found in US soldiers deployed in this country (86).…”
Section: Human Q Fever Is Found On Six Of Seven Continents: An Epidemmentioning
confidence: 99%
“…In the Arabian Peninsula, the presence of C. burnetii in humans was reported in 1968, and a recent serological analysis detected C. burnetii Ig in 35.2% of patients with pyrexia of undetermined cause (83)(84)(85). In Qatar, Q fever data are rare, yet a seroprevalence of 2.1% was found in US soldiers deployed in this country (86).…”
Section: Human Q Fever Is Found On Six Of Seven Continents: An Epidemmentioning
confidence: 99%
“…The first reports on Q fever in humans in Saudi Arabia were published in 1966 and 1968 (Gelpi, 1966). American soldiers deployed to Iraq in 1995 had 10.6 seroconversions per 1,000 person-months (Royal et al, 2013). Less is known about Q fever than brucellosis, although both are endemic to Saudi Arabia and share similar transmission routes.…”
Section: Introductionmentioning
confidence: 99%
“…Royal et al ( 20 ) recently reported C. burnetii seroprevalence in US troops deployed to the Al Asad region of Iraq in 2005; a known Q fever outbreak occurred in this region at this time. This smaller study (n = 136) reported a 7.2% prevalence of C. burnetii infection among troops located in that area at the time of the outbreak.…”
Section: Discussionmentioning
confidence: 96%